1998
DOI: 10.1046/j.1365-2133.1998.02460.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma in the treatment of systemic sclerosis: a randomized controlled multicentre trial

Abstract: We report the results of a randomized controlled multicentre study on interferon-gamma (IFN-gamma) treatment of systemic sclerosis as determined by skin sclerosis, renal and other organ involvement, global assessment, subjective symptoms and quality of life. Forty-four patients were enrolled into the trial, 27 in the treatment group and 17 in the control group. All patients presented with type I or type II scleroderma. Twenty-nine patients (64%) finished the study. The mean duration of Raynaud's phenomenon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…IFN␥ may also have a favorable effect on patients with SSc (90)(91)(92)(93). The importance of Th1/Th2 cytokines in fibrosis is supported by the finding that MRL/lpr mice lacking the IFN␥ receptor gene exhibit a syndrome that resembles human SSc (94).…”
Section: T Cell Activation and Cytokine Production In Ssc Leading To mentioning
confidence: 55%
“…IFN␥ may also have a favorable effect on patients with SSc (90)(91)(92)(93). The importance of Th1/Th2 cytokines in fibrosis is supported by the finding that MRL/lpr mice lacking the IFN␥ receptor gene exhibit a syndrome that resembles human SSc (94).…”
Section: T Cell Activation and Cytokine Production In Ssc Leading To mentioning
confidence: 55%
“…Although the pathogenesis of SSc is still unknown, SSc can be considered a Th2 mediated disease, since its collagen synthesis has been shown to be activated by Th2 cytokines such as IL-4 (3, 4) and IL-6 (26). While previous studies demonstrated that IFN-␥ has been effective for SSc (27), its practical usage is limited because of its side effects (28). IL-12 has a strong effect on induction of IFN-␥ production in vivo.…”
mentioning
confidence: 97%
“…287,288 Randomized trials of D-penicillamine, interferon-␣, or methotrexate either are no better than placebo or improve skin score with little beneficial effect on visceral organ function. [289][290][291] An exception is pulse intravenous cyclophosphamide, which appears to ameliorate scleroderma-related pulmonary alveolitis. 292 Scleroderma may be a vasculopathy, connective tissue disorder, and/or immune-mediated disease.…”
Section: Autologous Hsct For Sclerodermamentioning
confidence: 99%